Cuidados paliativos : nível de conhecimento de residentes de um hospital do norte gaúcho - Lima, Willian Guerra de (2025)
Palliative care is an integrated approach, carried out for patients and their families who are facing an illness that puts the patient's life at risk. This treatment is often offered in a hospital setting, where residents are part of the team that provides this type of care. However, there may be a flaw in the training process of these professionals in relation to the care of patients who are suffering the consequences of a serious illness and who require palliative care. To assess the level of knowledge and treatment self-efficacy about palliative care among residents of a hospital in the northern region of Rio Grande do Sul, constitutes the general objective This was an observational, descriptive, and cross-sectional study conducted at a philanthropic hospital of medium and high complexity. The sample consisted of 99 individuals participating in residency programs. Data collection took place from October 1, 2024, to March 31, 2025, using the Palliative Care Knowledge and Self-Efficacy Questionnaire (BPW – BR) and a questionnaire containing participants' sociodemographic data. The results of this dissertation will be presented in the article “Palliative Care: Knowledge Level of Residents in a Hospital in Northern Rio Grande do Sul”, which will be submitted to a scientific journal. They will also be featured in the book chapter “Palliative Care in Elderly Patients with Dementia”, published in the book Musculoskeletal Dysfunctions: Prevention and Rehabilitation. The residents demonstrate a good level of knowledge and self-efficacy regarding palliative care.